Older adults’ self-perception, technology anxiety, and intention to use digital public services - Jing An; Xuanyu Zhu; Kexin Wan; Ziyue Xiang; Zhan Shi; Jinlong An; Weidong Huang (BMC Public Health)
Abstract To improve the happiness of the older adults enjoying digital public services, this study examines the structural relationship among self-perception of aging, subjective well-being, technology anxiety, self-efficacy, perceived usefulness, and intention to use digital public services for older adults in the context of digital public services. We employ Structural Equation Modeling (SEM) for empirical analysis (N = 345, February to October 2023). The negative self-perception of aging may lead to the negative emotions of older adults on technology, which will reduce subjective well-being and increase technology anxiety. Technology anxiety indirectly affects the intention to use digital public services, which has an impact on the intention to use through the perceived usefulness and the complete mediating path of self-efficacy and perceived usefulness. Perceived usefulness is the most important factor affecting the behavior intention of older adults to use digital public services. Our study would provide reference to promote older adults’ digital literacy and silver happiness and promote the development of the silver digital economy.